2018
DOI: 10.7554/elife.38839
|View full text |Cite
|
Sign up to set email alerts
|

The cargo receptor SURF4 promotes the efficient cellular secretion of PCSK9

Abstract: PCSK9 is a secreted protein that regulates plasma cholesterol levels and cardiovascular disease risk. Prior studies suggested the presence of an ER cargo receptor that recruits PCSK9 into the secretory pathway, but its identity has remained elusive. Here, we apply a novel approach that combines proximity-dependent biotinylation and proteomics together with genome-scale CRISPR screening to identify SURF4, a homologue of the yeast cargo receptor Erv29p, as a primary mediator of PCSK9 secretion in HEK293T cells. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 58 publications
10
86
1
Order By: Relevance
“…However, this selectively may only be the result of differences in the expression profiles of Sec24A and Sec24B. Consistent with this idea, Sec24A exhibits 5‐ to 10‐fold higher expression as compared to Sec24B in the mouse liver . Similarly, conditional deletion of Sec24C in murine neural progenitors results in extensive neuronal cell death, but the phenotype can be rescued by ectopic expression of Sec24D …”
Section: The Copii Coatmentioning
confidence: 77%
See 1 more Smart Citation
“…However, this selectively may only be the result of differences in the expression profiles of Sec24A and Sec24B. Consistent with this idea, Sec24A exhibits 5‐ to 10‐fold higher expression as compared to Sec24B in the mouse liver . Similarly, conditional deletion of Sec24C in murine neural progenitors results in extensive neuronal cell death, but the phenotype can be rescued by ectopic expression of Sec24D …”
Section: The Copii Coatmentioning
confidence: 77%
“…Additionally, other cargo binding domains may exist on each Sec24 paralog, further expanding their ability to capture a multitude of cargoes . Although Sec24A and Sec24B exhibit significant overlap in cargo selectivity, mutational analysis in mice has uncovered a potentially unique role for Sec24A in PCSK9 secretion, a key regulator of plasma cholesterol levels, which is mediated by the PCSK9 receptor Surf4 . However, this selectively may only be the result of differences in the expression profiles of Sec24A and Sec24B.…”
Section: The Copii Coatmentioning
confidence: 99%
“…The embryonic lethality of SURF4 may therefore result from additive effects of disrupted secretion of known cargoes, or the presence of additional unknown SURF4 cargoes or functions that are essential for early embryonic development. A role for SURF4 in global protein secretion is unlikely, as previous studies demonstrated no effect of SURF4 deletion on the secretion of a number of other proteins 3,4 . A broader role for SURF4 in the secretion of additional unknown cargoes however is suggested by the observation that SURF4 has been evolutionarily conserved in ancient organisms lacking homologues of the putative mammalian cargo, PCSK9.…”
Section: Discussionmentioning
confidence: 92%
“…Deficiency of the SURF4 homologue SFT-4 is similarly associated with embryonic lethality in C. elegans 5 , but SURF4 is not essential for cellular viability in cultured HEK293T cells 3,4 and its homologue, Erv29p, is dispensable in yeast 24,25 . Deficiencies of PCSK9 or apoliporotein B alone cannot account for this developmental phenotype, given that PCSK9 -/mice are viable 26 and that ApoB -/mice survive past E9.5 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation